TANGGUNG JAWAB DIREKSI DALAM KEPAILITAN PERSEROAN TERBATAS - Suryadi, Asep (Jurnal Wawasan Yuridika, 2012)
Management is an organ which represents a companys interest as an independent legal subject. The management authority of a company is based on the of fiduciary duties principle, that is to say a principle which comes out as job and position are given to the management by the company. Pertaining to representative relationship between management and company, the performance of management in the framework of fiduciary duties principle shall bind the company and shall not bind the management personally. Nevertheless, when the management commits a violation against its principle, the management can be asked for personal responsibility. Members of management are not responsible for company bankruptcy if they can prove that it is not their failure or negligence as long as they are able to manage the company carefully, have full responsibility in behalf of the companys interest and go along with the companys goal, and they do not have any clash of interest directly or indirectly of what they have performed. But, the members of management can be asked for responsibility personally, when the company bankrupts as the result of their failure or negligence in running the management and their capacity as the representative of the company limited causing the companys bankruptcy.Keywords: management, responsibility, company.